Penerapan Pendekatan Keterampilan Proses Sains dalam Meningkatkan Hasil Belajar IPA Siswa SMP Negeri 4 Wera: Application of Science Process Skills Approach in Improving Science Learning Outcomes of Students of SMP Negeri 4 Wera - Yunita Mawardah; Olahairullah Olahairullah; Ariyansyah Ariyansyah (Universitas Jambi, 2021)
Efforts to improve the quality of education carried out by the government are improving the quality of teachers. Teachers must be able to direct the learning process by creating appropriate learning experiences, encouraging students to be active and critical, and providing easy learning for students in order to develop their potential optimally. This study aims to improve science learning outcomes for SMP Negeri 4 Wera students by applying a science process skills approach. The research design used was Kemmis and Taggart class action research. The results showed that the mastery of learning outcomes and classical completeness in the first cycle were in a complete category. The learning outcomes of the first cycle were 73.67%, and the classical completeness of the first cycle was 85.71%. In cycle II, the mastery of learning outcomes and classical completeness were also in the complete category. The cycle II learning outcomes were 95.23%, and classical completeness was 77.85%. Based on the analysis and testing results, it can be concluded that there was an increase in student learning outcomes using the science process skills approach in Class VIIA of SMP Negeri 4 Wera.